GAMBARAN KONDISI RANTAI DINGIN VAKSIN IMUNISASI DASAR DI PUSKESMAS KOTA SEMARANG - Tri Amelia Rahmitha Helmi; Lintang Dian Saraswati; Nissa Kusariana; Ari Udiyono (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
Vaccine cold chain is a procedure that is used to keep vaccines at a certain temperature. The aim was to describe the vaccine cold chain management of basic immunization program. The research was a descriptive observasional in 37 Semarang City health cares. Data were collected by conducting interview and observation to vaccine coordinators in each health cares in Maret – December 2018. The result showed officers used genset in emergency situation (75.5%), vaccines keeped in temperature +2˚C - +8˚C (67.5%), officers took sample per doos to check VVM (83.8%), used vaccine with VVM A first then B (83.8%), did not use vaccine with VVM C or D (86.5%), used vaccine by FIFO principle (89.2%) used vaccine by EEFO principle (97.3%), used vaccine after immunization (94.6%), arranged vaccine by expired date (94.6%) and by type of vaccine (64.9%), maintained refrigerator with defrosting (40.5%), monitored temperature in off day (2.7%), record temperature twice a day (73.0%), did not meet another thing in refrigerator (97.3%), spaced refrigerator 15 cm from the wall (24.3%), and made cool pack in another refrigerator (73.0%). The conclusion was no vaccine immunization program management in Semarang that managed according to Ministry of Health Regulations number 12/2017 on the Implementation of immunization. Officer recommended to defrosting refrigerator regularly and space the refrigerator to wall.